Time constraint route search over multi-locations. (21st March 2014) - Zhao, Geng; Xuan, Kefeng; Taniar, David; Safar, Maytham; Srinivasan, Bala
Abstract: Traditional Route Search aims at finding the path that goes through geographical entities that are relevant to the provided search terms from the start point to the end point. Without constraints, traditional Route Search visiting multiple locations is unreliable because locations may close after a specified time. In this paper, time constraint (operating hours of each location) is drawn into Route Search query in order to make the query more realistic. Two methods are proposed in this paper, namely Route Search for fixed locations ( RFix ) and Route Search for flexible locations ( RFlex ). These two queries are different from the existing Route Search query because (1) the end point is not pre-defined and (2) time constraint is involved. Our two proposal queries consider whether the locations are specifically pre-defined by the user or only the location types are specified. In each method, two propositions are presented for pruning expansion branches, which highly improves the performance. Our experiments verified the applicability of RFix and RFlex to solve Route Search queries with time constraint queries.